A novel anti-CD47 antibody with therapeutic potential for NK/T-cell lymphoma - Liping Qin; Yajun Li; Ruolan Zeng; Yizi He; Xiaoyan Chen; Ling Xiao; Hui Zhou (Human Vaccines & Immunotherapeutics)
NK/T-cell lymphoma (NKTCL) is a rare type of non-Hodgkin lymphoma (NHL). Although L-asparaginase-based chemotherapy has significantly improved survival in early-stage patients, the prognosis is poor in advanced and relapsed or refractory patients. CD47 is a promising target for cancer immunotherapy. However, the expression of CD47 in NKTCL and the antitumor effect and mechanism of the anti-CD47 monoclonal antibody (mAb) AK117 in NKTCL remain unclear. Firstly, the expression level of CD47 protein in NKTCL cells was detected by immunoblot and flow cytometry. Secondly, in order to validate the role of CD47 downregulation in the proliferation, apoptosis, and cell cycle of NKTCL cells, we used shRNA transfection to knock down CD47 expression. We determined the effect of knocking down CD47 and the novel anti‐CD47 antibody AK117 on the phagocytosis of NKYS and YTS cells by M2 macrophages in vitro. Finally, we assessed the ability of AK117 to inhibit tumor growth in an NKTCL xenograft model in which YTS cells were engrafted in SCID mice. The results showed that CD47 is relatively highly expressed in NKTCL cells. CD47 knockdown in NKTCL promoted phagocytosis by M2 macrophages in an in vitro coculture assay. The study also demonstrated that anti-CD47 mAb AK117 promoted phagocytosis of NKTCL cells by M2 macrophages. In addition, in vivo experiments showed that the anti-CD47 mAb AK117 significantly inhibited the growth of subcutaneous xenograft tumors in SCID mice compared to the control antibody IgG. Our results indicate that targeting CD47 monoclonal antibodies is a potential therapeutic strategy for NKTCL.